Respostas

2013-12-07T22:21:11-02:00
A)  \left \{ {{x + y = 15} \atop {x - y = 3}} \right.  
   2x = 18
                     x = 9

9 + y = 15
                      y = 6

b)  \left \{ {{3x + y = 24} \atop {x + y = 10}} \right. ( - 1)
  
3x + y = 24
- x - y = - 10
2x = 14
                      x = 7

7 + y = 10
                      y = 3 


c)  \left \{ {{3x + y = 8} \atop {x - 3y = 6}} \right. ( - 3)

3x + y = 8
- 3x + 9y = - 18

10y = -10 
                       y = - 1

3x - 1 = 8
3x = 9
                      x = 3
1 5 1
:D
pode deixar mais claro a letra b) ? nao da pra entender direito
ok
nao precisa mais já consegui entender
xau